(untitled) (Ustozlar uchun, 2026)
This article examines linguistic adaptation as a core strategy in video game localization. Drawing on translation studies, pragmatics, and intercultural communication theory, the paper investigates how source-language content — including dialogue, culturally embedded references, humor, and interface text — is restructured to achieve functional and cultural equivalence in target-language versions. The study analyzes adaptation strategies across lexical-semantic, pragmatic-functional, and sociocultural dimensions. The findings suggest that effective localization requires a dynamic balance between source fidelity and cultural resonance, positioning linguistic adaptation as a principled communicative strategy rather than a deviation from translation norms.